Ácido guanidinoacético em dieta pré-inicial para frangos - Borges, Kamilla Martins (2017)
Creatine is a substance that provides temporary energy. Guanidinoacetic acid (AGA) is a natural precursor of creatine, and can be added to feeds. The AGA provided acts as an energetic substrate with lower protein degradation with amino acid shift for gluconeogenesis, improving the initial performance of the birds. To evaluate the AGA in broiler chicken diet, an experiment was carried out using rations formulated for the pre-initial phase. Treatments consisted of a basal diet without AGA and rations with 0.10 and 0.20% AGA. A total of 252 male cutting chicks, distributed in a completely randomized design (DIC), with seven replicates and 12 birds per experimental unit were used. Feed consumption, weight gain and feed conversion were evaluated at seven, 14 and 21 days of age. Six days later, blood samples were collected for the determination of creatinine, creatine kinase (CK) and glucose and two metabolism tests were performed one at three and the other at 17 days of age. Data were submitted to analysis of variance ANOVA and the means were compared by the Tukey test. In the period of 1 to 7 days, an improvement in the feed conversion of animals receiving 0.20% AGA was observed. In the period from 7 to 14 days there was improvement in feed conversion and tending to improve the weight gain of the animals that received 0.20% AGA. There was no cumulative effect of AGA use on experimental rations fed to broiler chickens from 1 to 7 days of age on performance up to 21 days of age. Blood creatinine values at six days of life did not show significant differences. Animals that received 0.20% AGA presented higher CK blood concentration than the other treatments. The blood glucose concentration did not present statistical differences between treatments. The crude protein metabolism coefficient (CMPB) was increased within 3 to 7 days for animals receiving 0.20% AGA in the diet. There was no difference between treatments in the period from 17 to 21 days for the metabolization coefficient. The animals' intestinal weight and length did not show differences between treatments. Levels of 0.10 and 0.20% of AGA in the pre-starter diet improves weight gain and feed conversion over the period from 1 to 14 days of age in broilers.